P9 Weight loss as a predictor of mortality in patients with idiopathic pulmonary fibrosis: a retrospective study. (12th November 2019) - Vekaria, G; Murrells, T; Porter, J; Heightman, M; Sahota, J; Miklasch, T; Beitverda, L; Starodub, R
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) often leads to death from respiratory failure, but there is much variation in outcome between patients. Limited evidence suggests an independent relationship between body weight change and mortality in patients with IPF. 1, 2 Other prognostic biomarkers aid clinical decision making, and it is recognised that a decline in Forced Vital Capacity (FVC) of >10% in a year is a significant predictor of mortality in this disease. Objectives: To explore if weight loss independently affects mortality in individuals with IPF. Methods: Retrospective data were collected using electronic medical records on a sample of patients diagnosed with IPF at one tertiary care NHS teaching hospital in London, UK. Adult (≥18 y) patients diagnosed with IPF were included. Weight was collected at diagnosis and around 1 year after diagnosis together with details of comorbidities, medications, oxygen use, echocardiogram and pulmonary function tests. A significant body weight loss was defined as an annual body weight change of >5%. 2 Survival from 1 year after diagnosis onwards served as a primary endpoint in a multivariable Cox regression model. Results: A total of 205 patients diagnosed with IPF between 01/2017 and 12/2018 were included in the analysis. The mean age at diagnosis was 75.4±8.2 years and 172/205 (83.9%) were male. Median survival was 1172 days (95% CI 756 to 1589). Percent weight loss of 5% or more was associated with a shorter survival time (median 556 vs. 1548) compared to those who lost less weight. In the multivariable Cox regression model, only TLCO percent predicted at 1 year (p<0.001) and FVC decline of more than 10% in the last year (p=.011) were significantly associated with survival. Conclusions: Weight loss of 5% or more is independently associated with increased mortality of IPF patients. References: Alakhras M, et al . Body mass index and mortality in patients with idiopathic pulmonary fibrosis. Chest . The American College of Chest Physicians, 2007;131(5):1448–1453. doi: 10.1378/chest.06–2784 Nakatsuka Y, et al . The clinical significance of body weight loss in idiopathic pulmonary fibrosis patients. Respiration 2018;96(4):338–347. doi: 10.1159/000490355